To green or not to green : a study of moral and social factors influencing convenience in green purchase in a frugal society. - Hoe, Vinette. (2013)
This causal study intends to investigate the motivators of both frugal and non-frugal consumers for purchasing green in the context of convenience. The main objective is to provide green marketers, via our research findings, with an understanding of the influences, and to what extent do these influences affect convenience in green purchase for the frugal and non-frugal consumer. The revised conceptual framework consists of six independent variables - Altruism, Reciprocity, Social Justice, Social Recognition, Social Pressure, and Social Influence. Convenience in green purchase acts as the dependent variable. Two groups of consumers – the frugal and non-frugal – were used for comparison as to how the motivators differed. We developed 7 hypotheses for each of the consumer groups based on the conceptual framework.